Enterprise Architecture Design Using The Open Group Architecture Framework (TOGAF) at Logistic Courier Services - Johanes Fernandes Andry; David Sugian; Michael Kartin; Danu Pranamya (IT Journal Research and Development, 2023)
Logistics services are growing day by day in line with increasing consumer demand. This supports a new habit, namely express service delivery activities. All these delivery service activities require a structured system design so that users can use various kinds of logistics services. The role of enterprise architecture planning that can provide a framework as a reference for developing information systems, namely TOGAF (Open Group Architecture Framework). Through this research, it is hoped that the company can improve the effectiveness and efficiency of work in its business processes and integrate company systems that can support the company's business processes. Therefore, in this article, we will conduct an Enterprise Architecture Design Using the Open Group Architecture Framework (TOGAF) at Logistic Courier Services (LCS) Indonesia to identify problems. In the system, a blueprint is needed, because enterprise architecture planning can provide a framework as a reference for developing information systems. Through this article, LCS does not have serious problems in the system so that users do not feel so disturbed when using this logistics delivery service. However, there are still some things that must be improved and maintained to reduce errors when using this shipping service.